Vulnerability analysis of the economic-social-ecological complex system of Island tourism destinations - Mingya Zhang; Yetao Zhou; Senyao Sang (PLoS ONE, 2025)
Exploring the vulnerability characteristics of the economic-social-ecological complex system of island tourism destinations can provide better theoretical and practical guidance for the sustainable development of island tourism destinations. Taking Zhoushan, which is a famous island tourism destination in China, as a case, based on the vulnerability analysis framework of exposure, sensitivity, and adaptive capacity, this paper employs the entropy value method, comprehensive index method, system coordination degree model, and obstacle model to quantitatively measure the vulnerability of the economic-social-ecological complex system of Zhoushan from 2011 to 2022. It analyzes the spatial and temporal heterogeneity characteristics of the complex system`s vulnerability and the obstacle factors in the four administrative regions that make up the case site. The research results reveal that the vulnerability of Zhoushan’s economic-social-ecological complex system shows a decreasing trend, indicating its ability to withstand external disturbances continuously increases. However, the decline in the coordinated development of vulnerability reveals the imbalance in the development of internal systems among the four different regions. Furthermore, the study finds that the degree of obstacles to the ecological system is relatively high at the system level. In contrast, at the indicator level, the main obstacle factors are the total import and export trade, density of the tourism economy, construction land ratio, island land and sea area coefficient, and tourist density. Based on these findings, the study suggests deepening trans-regional cooperation, paying attention to constructing ecological systems and promoting the coordinated development of the island tourism destination complex system to reduce the overall vulnerability of island tourism destinations.